Innovative microscale workflow from fungi cultures to Cell Wall‐Degrading Enzyme screening. Issue 6 (20th April 2019) - Raulo, Roxane; Heuson, Egon; Siah, Ali; Phalip, Vincent; Froidevaux, Renato
Summary: This study aimed at developing a complete miniaturized high‐throughput screening workflow for the evaluation of the Cell Wall‐Degrading Enzyme (CWDE) activities produced by any fungal strain directly cultivated on raw feedstock in a submerged manner. In this study, wheat straw was selected as model substrate as it represents an important carbon source but yet poorly valorised to yield high added value products. Fungi were grown in a microbioreactor in a high‐throughput (HT) way to replace the fastidious shaking flask cultivations. Both approaches were compared in order to validate our new methodology. The range of CWDE activities produced from the cultures was assayed using AZO‐died and pNP‐linked substrates in an SBS plate format using a Biomek FXp pipetting platform. As highlighted in this study, it was shown that the CWDE activities gathered from the microbioreactor cultivations were similar or higher to those obtained from shake flasks cultures, with a lower standard deviation on the measured values, making this new method much faster than the traditional one and suitable for HT CWDE production thanks to its pipetting platform compatibility. Also, the results showed that the enzymatic activities measured were the same when doing the assay manually or using the automated method. Abstract : Workflow for fungi cultures and enzyme activities.